PENANGANAN LIMBAH GERGAJIAN BATU ALAM PASCA ERUPSI MERAPI - Saiful Huda; Aji Pranoto (Universitas Muhammadiyah Semarang, 2015)
Stone sawing process in the area of Sleman leaves stone powder as waste, which discharged directly onto the ground can result lead to severe environmental damage. To overcome this problem, was made natural stone sawmill waste for making handicrafts. The program is implemented with the main objective to empower people to be able to cope with waste and create new jobs. The resulting product consists of Crafts (handcraft), Flower Pot and Mosaic. The first is the handcraft produced with the main ingredient as the matrix is resin apoxy 95%, hardener 3%, plus 2% cobalt, as inforcement used stone dust particle with variable best comparison is 50% matrix, and 50% particle inforcment. whereas the mold to make handcraft materials using RTV silicone rubber 586 plus hardener. Both produced flowerpot with the main ingredient of cement and sawdust stone cast coupled with hardener (hardener), where the best compositions based on test results is 15% cement an d 75% stone dust. The molds used are made of Fiber Glass and steel molds. The resulting third is a mosaic, made of stone flakes aggregate prepared using cement and wire mesh material as a binder and stone chips as forming ornaments.Keywords: Natural Stone Powder, Flake Stone, Flower Pot, Handcraft, Mosaic.